Tempoyak Sebagai Faktor Risiko Kejadian Hipertensi (Studi pada Masyarakat Suku Dayak di Wilayah Puskesmas Tumbang Samba, Kabupaten Katingan, Kalimantan Tengah) - Dwi Sutiningsih; Inova Inova; Mateus Sakundarno Adi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Tempoyak is a traditional food of Dayak tribe that is processed from durian fruit meat. Some studies show that at a certain amount of tempoyak consumption can increase blood pressure. Nutritional content in durian fruit that can affect blood pressure, namely, potassium, calcium, sodium, and alcohol. The purpose of this study is to prove that consuming tempoyak is a risk factor for hypertension.Methods: This research is an observational research with cross sectional design that is done in Dayak tribal communities in the area of Tumbang Samba health center. The study population in this study is the population in the area of Puskesmas Tumbang Samba Katingan Regency. The sample number was 180 respondents who met the inclusion and exclusion criteria.Result: The results showed that the proven factors for the incidence of hypertension are coffee consumption (PR=5,280; p-value=0.022), tempoyak consumption frequency (PR=3,935; p=value=0.047).Conclusion : Tempoyak consumption is proven to be a risk factor for the incidence of hypertension.